2017
DOI: 10.1136/archdischild-2017-313266
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for performing voiding cystourethrogram: a randomised control trial

Abstract: Clinical Trial Registry of India: CTRI/2017/03/00824.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…In addition, the last method features urinary tract infection as a complication. 14 Here, we measured FBC using the 48-h F/V chart and UFM with PVR. There was no significant difference in the FBC values obtained from the two measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the last method features urinary tract infection as a complication. 14 Here, we measured FBC using the 48-h F/V chart and UFM with PVR. There was no significant difference in the FBC values obtained from the two measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…In children undergoing RUG or UDS, ppUTI was documented in 2.1% and 0-4.8% of cases, respectively. Larger variations were evidenced in studies enrolling children with VCUG and RNC, among whom ppUTI was diagnosed in up to 42% of children [14][15][16][17][18][19][20]. The highest values were reported in the oldest studies, while in the most recent evaluations incidence rates of ppUTI were found in the range already reported for the other imaging procedures with catheterization.…”
Section: Scenario #1 Imaging Procedures Involving the Urinary Tractmentioning
confidence: 98%
“…However, studies carried out in children undergoing imaging procedures requiring catheterization have shown that the risk of ppUTI is generally low, although with some exceptions [14][15][16][17][18][19][20]. In children undergoing RUG or UDS, ppUTI was documented in 2.1% and 0-4.8% of cases, respectively.…”
Section: Scenario #1 Imaging Procedures Involving the Urinary Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a randomized controlled trial on preventing VCUGrelated UTI, it is recommended to use antibiotics post-VCUG in patients with abnormal USG findings. 44 A 1% risk of post-VCUG UTI was reported for children with congenital urological anomalies, such as VUR or hydronephrosis. Particular care needs to be taken with VUR and/or hydronephrosis patients when carrying out VCUG.…”
Section: Complications Of Vcugmentioning
confidence: 99%